2021
DOI: 10.14710/jmr.v10i4.31679
|View full text |Cite
|
Sign up to set email alerts
|

Kerapatan dan Pola Sebaran Lamun Berdasarkan Aktivitas Masyarakat di Perairan Pengujan Kabupaten Bintan

Abstract: Penelitian ini bertujuan untuk mengetahui kerapatan, pola sebaran dan indeks ekologi lamun berdasarkan aktivitas masyarakat di Perairan Desa Pengujan. Pengambilan sampel dan data ditentukan dengan metode Purposive Sampling sepanjang 100 meter dari pertama bertemunya lamun menggunakan transek kuadrat berukuran 50x50 cm. Pengambilan data dilakukan pada 3 stasiun yang terdapat aktivitas masyarakat yaitu aktivitas penangkapan siput gonggong pada stasiun I, aktivitas tambatan perahu pada stasiun II, dan tidak ada a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Similar conditions can also be seen in the results of brightness measurements in seagrass beds in the waters of Pengujan District. Bintan is 100% or up to the bottom of the waters (Sari, et al ., 2021). This is related to seagrass habitat in shallow waters (Ariasari et al ., 2022).…”
Section: Discussion Basic Physico-chemical Parameters Of Water and Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conditions can also be seen in the results of brightness measurements in seagrass beds in the waters of Pengujan District. Bintan is 100% or up to the bottom of the waters (Sari, et al ., 2021). This is related to seagrass habitat in shallow waters (Ariasari et al ., 2022).…”
Section: Discussion Basic Physico-chemical Parameters Of Water and Su...mentioning
confidence: 99%
“…Dahuri (2003) stated Fisheries Journal, 14(2), 941-951. http://doi.org/10.29303/jp.v14i2.854 Wuru et al (2024) that a current speed of 0.5 m/s can support maximum seagrass growth. However, the range and average when compared with the current speed in other seagrass meadows tends to be higher than the current speed in the seagrass meadows of Pengujan Village Waters, which is around 0.021-0.052 m/s with an average of 0.04 m/s and the current speed 0.021 m/s tends to have a higher seagrass density than seagrass beds which have higher current velocities (Sari et al ., 2021). Salahuddi n et al .…”
Section: Discussion Basic Physico-chemical Parameters Of Water and Su...mentioning
confidence: 99%
“…Then when the conditions receded, station one area was still flooded with a little water so that the seagrass conditions were still wet and did not wither due to exposure to direct sunlight, while at station three at low tide the conditions were part of the area was almost dry so that many seagrasses withered due to exposure to direct sunlight. Judging from the substrate, stations one and two have sandy mud substrates, according to Supriharyono in (Sari, et al, 2021), in general, seagrass plant ecosystems with large expanses are found in thick sandy mud substrates. So seagrasses developed well at the station.…”
Section: Seagrass Densitymentioning
confidence: 99%
“…Berbeda halnya pola sebaran E.acoroides di Desa Garapia cenderung mengelompok (Moningka et al, 2018. Adanya perbedaan tersebut dimungkinkan adanya perbedaan karakteristik substrat dasar dan padang lamun di Desa Garapia disusun oleh 5 spesies (Cymodocea rotundata, Thalassia hemprichii, Halophila ovalis, Syringodium isoetifolium, dan Enhalus acoroides) sedangkan di padang lamun P. Badak Badak disusun oleh E.acoroides (monospesifik). Sari et al (2021) melaporkan bahwa pola sebaran E.acoroides di padang lamun Pengujan Kab. Bintan cenderung mengelompok, kondisi demikian didoroang oleh adanya kativitas Masyarakat yang meanfaatkan padang lamun sebagai daerah penangkapan siput Gonggong dan tambatan perahu serta teksture substrat dasar pasir berkerikil.…”
Section: Pola Sebaran Eacoroidesunclassified